Acute Presentation of a Pseudoaneurysm After a Proximal Humerus Shaft Fracture: A Case Report. Issue 1 (January 2020) - Manzano, Givenchy; Brown, Corina; Harth, Karem; Ochenjele, George
Abstract : Case: A 69-year-old woman presented with a brachial artery pseudoaneurysm causing median, ulnar, and radial nerve compressive neuropathies 8 weeks after a proximal humerus shaft fracture treated with intramedullary nailing. She underwent a brachial artery bypass with a reverse cephalic vein interposition graft and neurolysis after decompression of a large pseudoaneurysm. Postoperatively, the patient had a normal vascular examination with recovering neurological function. Conclusions: A high index of suspicion for a brachial artery pseudoaneurysm should be maintained in patients with a displaced proximal humerus shaft fracture, particularly when an abnormal neurovascular examination is present.